STRATEGI GURU EKONOMI MENGGUNAKAN MEDIA PEMBELAJARAN ALTERNATIF PADA SEKOLAH DENGAN PEMBATASAN GAWAI - Auliya Anjani, Ayu; Ekbal Santoso; Muhammad Anasrulloh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The policy of restricting student device use at MA Darul Hikmah Tulungagung encourages economics teachers to develop alternative, non-digital learning media to ensure effective learning. This study aims to analyze economics teachers' strategies in using alternative learning media, including media types and characteristics, design and implementation processes, student responses and involvement, and obstacles and solutions. The study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that teachers used visual media in the form of images and "Question" and "Challenge" cards designed based on the principles of simplicity, emphasis, and balance, and adapted to student characteristics and learning objectives. The use of these media received a positive response, demonstrated by increased student motivation, attention, participation, and engagement in economics learning. Challenges encountered included adapting the media to student characteristics and the need for preparation time. These obstacles were overcome through thorough media planning, material adjustments, and mentoring during learning. These findings suggest that alternative learning media can be an effective strategy in schools with device restrictions.